Expression of TLR4 mRNA in lungs of mice after single and multiple exposures to poultry barn air - PALLVI; SETHI, R S; MUKHOPADHYEY, C S; RAMNEEK, RAMNEEK (The Indian Journal of Animal Sciences, 2016)
The poultry sector in India being a commercial activity requires workers to spend more number of hours inside the barns. The exposure of workers to barn air may also increase susceptibility to secondary microbial challenges. However, there are no data on the health effects of exposure to the barn from tropical climates. Because of the central role of the toll like receptor 4 (TLR-4) in endotoxin-induced lung inflammation, we evaluated expression of TLR-4 following single and multiple exposures to poultry barn air followed by lipopolysaccharides (LPS) challenge. Male mice (80) aging 7-8 weeks were divided into 4 groups, viz. 3 treatments and 1 control (20; each). Among the treatment groups, Group 1 was exposed to poultry barn air for single day, group 2 for 6 days (Mon to Sat) and group 3 for 24 days (4 weeks, Mon to Sat) for 8 hrs. At the end of exposure period, half of the animals (10) from each group were challenged with LPS @ 100µg/ animal. Immediately following sacrifice, the lung tissues were collected to study the expression profile of TLR-4 mRNA by quantitative RT- PCR. Single exposure did not show any significant change in the expression of TLR-4 mRNA, while 6 days multiple exposures resulted in almost 6 fold increase in the expression of TLR-4 mRNA. There was no change in the expression of TLR-4 mRNA after 24 days multiple exposures compared to control suggesting that prolong multiple exposures may induce adaptation. However, single and 6 and 24 days multiple exposures followed by LPS challenge showed 6, 47 and 17 fold increase in the expression of TLR-4 mRNA, respectively. The data showed exposure to poultry barn air alters TLR-4 expression which may underlie altered responsiveness to LPS challenge.